INFLUENCE OF PIRATED FILMS ONLINE ON THE POPULARITY OF FILM FOR SOME STUDENTS IN BANDUNG - Riyu Wansyah (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Although technological advances can have a positive impact, but can also have a negative impact on the field of film, namely the rise of film piracy by irresponsible individuals. Increasingly stable internet access, plus the number of movies that are now being shown through digital platforms make it easier for perpetrators to commit these criminal acts, plus the increasing number of movie enthusiasts who prefer to watch or download pirated films rather than buying official films or licensed films become a great opportunity for movie pirates to continue committing these crimes. The study was conducted to investigate the reasons why people would rather watchpiratedmovies than buy official or licensed movies. This research uses a quantitative approach that is descriptive, with data retrieval techniques carried out by researchers, namely data collection techniques by spreading questions with the help of google form. The criteria of respondents who can qualify are students who can use the internet and have done digital piracy, especially in the field of film (downloading from the internet).